Integratedly analyzed quantitative proteomics with transcriptomics to discover key genes via fg-1 non-heading mutant in the early heading stage of Chinese cabbage - Li, Jingrui; Fan, Mi; Zhang, Xiaomeng; Yang, Liling; Hou, Guangguang; Yang, Lei; Li, Na; Xuan, Shuxin; Zhao, Jianjun (Frontiers in Plant Science, 2024)
Leaf heading is an important agronomic trait of Chinese cabbage directly affecting its yield. The leaf-heading formation of Chinese Cabbage is controlled by its internal genotype and external environmental factors, the underlying mechanism remains poorly understood. To discover the leaf heading formation mechanism more deeply, this study analyzed the correlations between proteomic and transcriptomic data in the leaf heading formation mutant fg-1 generated by EMS. iTRAQ-based quantitative proteomics techniques were performed to identify the protein expression profiles during the key periods of the early heading stage in the section of the soft leaf apical region (section a) and the whole leaf basal region (section d). We first identified 1246 differentially expressed proteins (DEPs) in section a and 1055 DEPs in section d. Notably, transcriptome-proteome integrated analysis revealed that 207 and 278 genes showed consistent trends at the genes' and proteins' expression levels in the section a and section d, respectively. KEGG analyses showed phenylpropanoid biosynthesis pathway were enrichment both in the section a and d. Furthermore, 86 TFs exhibited co-upregulated or co-downregulated and 7 out of 86 were involved in plant hormone synthesis and signal transduction pathways. This indicates they are potentially related to the leaf heading formation in Chinese cabbage. Taken together, we have idetified several key early heading formation related factors via integration analysis of the transcriptomics and proteomics data. This provides sufficient gene resources to discover the molecular mechanism of leaf heading formation.